1999
DOI: 10.1093/toxsci/51.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke exposure produces more evidence of emphysema in B6C3F1 mice than in F344 rats

Abstract: Cigarette smoke (CS) causes pulmonary emphysema in humans, but results of previous studies on CS-exposed laboratory animals have been equivocal and have not clearly demonstrated progression of the disease. In this study, morphometry and histopathology were used to assess emphysema in the lungs of B6C3F1 mice and Fischer-344 rats. The animals were exposed, whole-body, to CS at a concentration of 250 mg total particulate matter/m3 for 6 h/day, 5 days/week, for either 7 or 13 months. Morphometry included measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 32 publications
2
52
0
Order By: Relevance
“…After an acclimatization period, mice were placed in wire-bottomed cages in the smoke exposure chamber. The mice were exposed to diluted and slightly aged mainstream cigarette smoke generated from burning 1R3 reference cigarettes (Kentucky Tobacco Research and Development Center, University of Kentucky, Lexington, KY) as described previously (5,16). Mice were exposed to smoke concentrations of 100 mg total particulate matter/m 3 for the first week, and then the concentration was increased to 250 mg total particulate matter/m 3 for the remainder of the exposure.…”
Section: Methodsmentioning
confidence: 99%
“…After an acclimatization period, mice were placed in wire-bottomed cages in the smoke exposure chamber. The mice were exposed to diluted and slightly aged mainstream cigarette smoke generated from burning 1R3 reference cigarettes (Kentucky Tobacco Research and Development Center, University of Kentucky, Lexington, KY) as described previously (5,16). Mice were exposed to smoke concentrations of 100 mg total particulate matter/m 3 for the first week, and then the concentration was increased to 250 mg total particulate matter/m 3 for the remainder of the exposure.…”
Section: Methodsmentioning
confidence: 99%
“…However, they appear to be relatively resistant to the induction of emphysema-like lesions. Using morphometry and histopathology to assess and compare emphysema development in mice and rats, significant differences were demonstrated [214]. In B6C3F 1 mice, many of the morphometric parameters used to assess emphysema-like lesions differed significantly between exposed and nonexposed animals.…”
Section: Variability Of Response In Micementioning
confidence: 99%
“…Enlarged alveolar spaces and increased alveolar duct area are found after 3-6 months of tobacco smoke exposure in susceptible strains, such as B6C3F 1 mice [214]. The length of time required to produce emphysema is usually .4 months, depending upon the method of exposure, cigarette dose and species [215][216][217].…”
Section: Variability Of Response In Micementioning
confidence: 99%
“…The number of recent reports on the pathophysiology of emphysematous animal models has increased rapidly, but none of them has tested the presence of hypercapnia/hypoxemia ( (Mahadeva et al 2002), see discussion in reference (March et al 2006b)). The emphysema of C3H/HeN, A/J, and C57BL/6 mice induced by chronic CS exposure (16 wk) has been investigated, and the results shown that the emphysema susceptibility among these strains has been ranked as C3H/HeN > A/J > C57BL/ 6; female mice are particularly affected (March et al 1999(March et al , 2006a(March et al , 2006bGuerassimov et al 2004). Thus, we hypothesized that female C3H/HeN mice chronically exposed to CS would display the major characteristics seen in hypercapnic COPD patients, including: (1) emphysema, (2) hypercapnia, (3) rapid breathing at rest, and (4) AVR to hypoxia and hypercapnia.…”
Section: Introductionmentioning
confidence: 99%